The Moderation of Da’wah in Empowering Islamic Lifestyle - Zulkifli Abdul Ghani, Mohamad; Dardaa Mohamad, Abu; Hilmi Wan Abdullah, Wan; Arif Yahya, Muhammad; Ghafar Don, Abdul; Huda, Miftachul; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
Islam belongs to all people regardless of race, colour and culture. Muslims have a distinctive lifestyle that possesses good values and behaviour through the Islamic teaching. But today the Islamic lifestyle is seen as oblique and is considered outdated by some. This paper focused on the moderation of da’wah in order to build an Islamic lifestyle. Therefore, to ensure that Islamic lifestyle has a place in the society today, it needs to be presented based on the moderation of da’wah (wasatiyyah al-da’wah). The moderation of da’wah should be seen as a foundation in building an Islamic lifestyle that stands for noble Islamic teachings. To ensure the success of the Islamic lifestyle practice, the moderation of da’wah begins in one’s life with understanding the five types of Islamic jurisprudence, understanding the reality (al-waqi’), tolerating disagreements (ikhtilaf), understanding the immutable (thawabit) and immutable (mutaghayyirat), as well as the suitability of approach to society and good management of dissemination. The real and actual understanding of the religion of Islam will be misplaced and lead to a misunderstanding if the moderation of da’wah is not understood and appreciated. It can even lead to nonIslamic lifestyle. Therefore, the moderation of da’wah is vital to ensure that Islamic lifestyle is well practiced in the society.